The potato R10 resistance specificity to late blight is conferred by both a single dominant R gene and quantitative trait loci - Xu, Jianfei; Wang, Jiajia; Pang, Wanfu; Bian, Chunsong; Duan, Shaoguang; Liu, Jie; Huang, Sanwen; Jin, Liping; Qu, Dongyu (Plant breeding, 2013)
The R10 late blight differential of potato, 3681ad1, exhibits good field resistance. Progeny from the cross between 3681ad1 and the susceptible cultivar ‘Katahdin’ were assessed for late blight resistance to three Phytophthora infestans isolates, using a detached leaf assay. Progeny differed in response to the three isolates. Resistance to isolates IPO‐0 and 99018 was controlled by quantitative trait loci (QTL), whereas resistance to isolate 89148‐9 was inherited as a dominant R gene, designated as R10 in this study. Statistical analysis revealed that one of the resistance QTLs to isolates IPO‐0 and 99018 is linked to the R10 gene, which maps to chromosome 11 in a region where a complex late blight resistance locus has been reported previously. A high‐resolution map of R10 was constructed using a large segregating population, and the gene was delimited to a genetic interval of 0.26 cM. The clustering of the qualitative gene R10 with resistance QTLs could explain the field resistance observed with 3681ad1.